Systematic Appraisal of the Role of Metallic Endobiliary Stents in the Treatment of Benign Bile Duct Stricture - Siriwardana, H P. Priyantha (2005)
OBJECTIVE: To carry out a systematic appraisal of the current status of the use of metallic endobiliary stents in the treatment of benign biliary strictures. METHODS: A computerized search of the MEDLINE and EMBASE databases identified 37 studies providing detailed clinical course data on outcome of metallic endobiliary stent placement in 400 patients. Pooled data were examined for etiology of stricture, indications for stent placement, procedure-related complications, and outcome with reference to stent patency. RESULTS: The median (range) number of patients per report was 8 (2–54) with a median recruitment period of 44 (9–126) months. The most frequent indications were postoperative biliary strictures in 123 (31%), stenosed biliary-enteric anastomoses in 79 (20%), and biliary strictures following liver transplantation in 88 (22%). During a median follow up of 31 (1–111) months, 139 (35%) stents occluded, and there are little patency data beyond 2 years after deployment, with 99 (25%) known to be patent at 3 years from stent placement. CONCLUSIONS: These pooled data on 400 patients constitute the largest collective report to date on the use of metallic endobiliary stents for benign biliary strictures. The results show a critical lack of data on long-term patency such that at the present time, metallic endobiliary stents should not be used for benign stricture in those patients with a predicted life expectancy greater than 2 years.